Four Europes: Climate change beliefs and attitudes predict behavior and policy preferences using a latent class analysis on 23 countries. (June 2022) - Kácha, Ondřej; Vintr, Jáchym; Brick, Cameron
Abstract: Building public will for climate action requires designing messages for different audiences. Previous studies that identified groups based on similar beliefs, behavior, and political preferences related to climate change were in single countries. The current pre-registered study ran latent class analysis on the European Social Survey (ESS 2016; N  = 44, 387) to identify groups of people according to their climate change attitudes and beliefs in 22 European countries and Israel. We found strong evidence for four groups: Engaged (18%), Pessimistic (18%), Indifferent (42%), and Doubtful (21%) and we compare the segment structure and proportions within Europe and to other countries. We identify differences between the groups in values, life satisfaction, and social trust, and then revealed that the groups uniquely predict self-reported behaviors not included in the segmentation. The findings characterize climate change beliefs for all of Europe and guide governments and pan-European bodies in designing effective communications to promote climate beliefs and actions. Highlights: Latent class analysis on the European Social Survey identified four groups of people by climate change attitudes and beliefs. Strong evidence for four groups: Engaged (18%), Pessimistic (18%), Indifferent (42%), and Doubtful (21%). The four groups uniquely predict self-reported behaviors not included in the segmentation. The relative group size can be tracked as an index of Europe-wide attitudes about climate change.